Men and Women Language Features on Joe Biden’s and Kamala Harris’s Speeches - Bagaskoro, Gilang (Politeknik Harapan Bangsa Surakarta, 2022)
This paper mainly investigates the use of male and female language features, especially in Joe Biden and Kamala Harris’s victory speeches. The use of these language features is seen from several aspects, including vocabulary, attitudes, syntax, as well as other aspects such as the choice of diction whose meaning is studied by semantics. This research includes qualitative research. The data was collected through transcripts of speeches downloaded from the internet. The results showed that every language feature possessed by gender will adapt to the context, condition, time, and form of communication, so it cannot be applied to all features in speech considering speech as a form of one-way communication. Keywords: language features, men and woman, speech